2019
DOI: 10.1007/978-3-030-23173-6_19
|View full text |Cite
|
Sign up to set email alerts
|

Golgi Structure and Function in Health, Stress, and Diseases

Abstract: The Golgi apparatus is a central intracellular membrane-bound organelle with key functions in trafficking, processing, and sorting of newly synthesized membrane and secretory proteins and lipids. To best perform these functions, Golgi membranes form a unique stacked structure. The Golgi structure is dynamic but tightly regulated; it undergoes rapid disassembly and reassembly during the cell cycle of mammalian cells and is disrupted under certain stress and pathological conditions. In the past decade, significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 349 publications
(321 reference statements)
0
73
0
Order By: Relevance
“…These new findings reveal novel roles for GRASPs in cellular activities outside of the Golgi. While some of these findings have been recently reviewed elsewhere (Li et al, 2019a), several key advances are discussed below in detail.…”
Section: New Discoveries On Grasp55 and Grasp65 Interacting Proteinsmentioning
confidence: 99%
“…These new findings reveal novel roles for GRASPs in cellular activities outside of the Golgi. While some of these findings have been recently reviewed elsewhere (Li et al, 2019a), several key advances are discussed below in detail.…”
Section: New Discoveries On Grasp55 and Grasp65 Interacting Proteinsmentioning
confidence: 99%
“…Expression of non-phosphorylatable GRASP65 mutants enhances Golgi stacking in interphase and inhibits Golgi disassembly in mitosis . Because GRASPs play critical roles in Golgi structure formation, it is reasonable to speculate that physiological and pathological cues may trigger Golgi fragmentation through GRASP55/65 modification, such as phosphorylation (Ahat et al, 2019a;Li et al, 2019a). Using GRASPs as tools to manipulate Golgi stack formation, it has been demonstrated that Golgi cisternal unstacking accelerates protein trafficking but impairs accurate glycosylation and sorting (Bekier et al, 2017;Xiang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Golgi apparatus is one of the most complicated organelles in the cells. More and more researches are focused on the morphology and function changes of Golgi in some oxidative stress related diseases[ 1 , 5 , 6 ]. However, the molecular mechanisms and its relative physiological functions of the Golgi stress has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that Golgi complex is relevant to the ion homeostasis, cell apoptosis, antioxidation, and stress sensing[ 4 ]. The integrated structure and steady function of Golgi apparatus could be impaired under oxidative stress, DNA damage and pro-apoptotic conditions, which may even induce Golgi fragmentation and cell apoptosis[ 5 , 6 ]. Therefore, the Golgi complex has become a new candidate for the research and therapy about oxidative stress-associated diseases.…”
Section: Introductionmentioning
confidence: 99%